Estágio profissional: O caminho de desenvolvimento profissional de um estudante estagiário rumo à promoção da aprendizagem dos alunos - Nuno Miguel Pinto da Silva (2022)
The professional school placement is fundamental in the process of professional training of a physical education teacher. The fact of reflecting theory in practice, being accompanied by competent professionals such as the cooperating teacher at school, and in the faculty context by the supervisor, makes the lived experiences more enriching and profitable. This report presents a description of my path, focusing, above all, on this year of school placement, where I discuss how I implemented the knowledge acquired during my training, as well as the difficulties felt during the school placement practice. Despite there being initial fears about possible limitations caused by the pandemic context, it turned out to be a year of fresh start where everything that was planned went without obstacles. All this allowed the development of face-to-face work in order to involve students in the process throughout the year, allowing the adoption of the best strategies for transmitting knowledge. This school year was quite challenging in itself, as the theory cannot foresee all practical situations, leading me to have to adapt and readjust to the plans in order to improve my performance and, consequently, contribute to student learning. Finally, and to conclude, a research study was carried out, in which we tried to understand, during the teaching of a volleyball unit, how the tasks influence the teacher's specialized content knowledge. KEYWORDS: